COVID-19 and Rheumatic Diseases in Tamil Nadu – A multicenter retrospective observational study - Sowndhariya V Annamalai; Sham Santhanam; Kavitha Mohanasundaram; Thilagavathy Nambi; Sriram Sankaran; Raja Natarajan; Prithvi Mohandas (Indian Journal of Rheumatology)
Aim: To describe the clinical and demographic characteristics of rheumatic disease patients who were diagnosed with COVID-19 infection. To identify the risk factors associated with hospitalization of patients and find out differences if any between patients managed as in-patients and out-patients. Methods: This was a multi-center retrospective observational study done by the analysis of data collected from six tertiary care centers from April 1, 2020, to October 15, 2020. All consecutive patients with a confirmed diagnosis of rheumatic disease and with a recent history of COVID-19 illness were included in the study. Results: Our study had a total of 85 patients with 58 managed as inpatients and 27 as outpatients. Six patients needed intensive care management and two patients succumbed to the illness. The majority were females (62/85) and majority (80/85) tested positive by the Reverse transcriptase-polymerase chain reaction method. The common rheumatic disease was rheumatoid arthritis (51.7%) followed by systemic lupus erythematosus (15.2%), psoriatic arthritis (10.5%), and others. Thirty-seven patients were on steroids and 28 were on hydroxychloroquine. There was no statistical difference in the mean dose of disease-modifying drugs between the two groups. Out of hospitalized people, 84.4% were above 40 years. There was a higher prevalence of comorbidities among hospitalized patients which was statistically significant (Chi-square test, P = 0.029). There was a positive correlation between duration of stay and steroid dose (Spearman rank correlation, “r” = 0.232), which was statistically significant (P = 0.03). There was no association between stay duration and other disease-modifying agents. Conclusion: There was a positive and statistically significant correlation between steroid dose and duration of stay. The prevalence of comorbidities was higher among hospitalized patients. There was no correlation between other immunosuppressive drugs and stay duration nor was there any difference in mean dosages of these drugs between patients treated as in-patients and out-patients.